2005
DOI: 10.1116/1.1924468
|View full text |Cite
|
Sign up to set email alerts
|

Structure and magnetic properties of Cr-doped GaN

Abstract: Structure and magnetic properties of the Ga1−xCrxN (x=0.013, 0.063, and 0.101) have been investigated. The lattice constant of the c axis is systematically decreased with increasing Cr content. The local structure around a Cr atom maintains tetrahedral symmetry up to x=0.101 the same as the local symmetry of GaN by x-ray absorption fine structure analysis. The analysis on x=0.013 indicated that the second nearest neighbor around the absorbing Cr atoms consists of only 12Ga atoms. However, for x=0.063, the seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
16
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 20 publications
6
16
1
Order By: Relevance
“…The Cr 2p spectrum of Cr 2 O 3 (Cr 3+ ) [17] is also shown for comparison. The peak position for GaCrN is close to that for Cr 2 O 3 , indicating that the valence of Cr in GaCrN is close to 3+, that is, the Cr atom is doped into GaN as a neutral impurity if Cr substitutes for Ga, consistent with the earlier reports [6,7,18] ducting GaN samples insulating [7,19]. The amount of the peak shift of each core level relative to that in GaCrN is plotted in panel (e).…”
supporting
confidence: 76%
See 2 more Smart Citations
“…The Cr 2p spectrum of Cr 2 O 3 (Cr 3+ ) [17] is also shown for comparison. The peak position for GaCrN is close to that for Cr 2 O 3 , indicating that the valence of Cr in GaCrN is close to 3+, that is, the Cr atom is doped into GaN as a neutral impurity if Cr substitutes for Ga, consistent with the earlier reports [6,7,18] ducting GaN samples insulating [7,19]. The amount of the peak shift of each core level relative to that in GaCrN is plotted in panel (e).…”
supporting
confidence: 76%
“…The calculated moments of the Cr-rich clusters with various sizes are 0.06-1.47 µ B /Cr, corresponding well to the observed M S ∼0.25 µ B /Cr. Kim et al [7] have reported that the M S of Ga 1−x Cr x N decreases with increasing Cr concentration, which can be interpreted as due to the size increase of the antiferromagnetic Cr-rich clusters. As for Zn 1−x Co x O, for which even smaller M S has been reported, Dietl et al [25] attributed the origin of the small M S to the uncompensated moments of the Co-rich AFM nanoclusters.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of a pre-edge peak in Cr K-edge spectrum demonstrates that Cr does not substitute on a tetrahedral Ga or vacancy site, as it does in Cr:GaN 33 or Cr:ZnTe, 18 and the energy of the edge is consistent with a formal valence of Cr 2+ (as in CrSe) and/or Cr 3+ (with Se neighbors screening more efficiently than oxygen). The Cr 2p absorption (Fig.…”
Section: A Structurementioning
confidence: 76%
“…[13,14], peak A in Fig. 2(a1) was due to the transition from Cr 1s electron to Al 3d-O 4p hybridized states occurring in low symmetry ligand fields such as the tetrahedral ligand field [15,16]. In the N K-edge XANES spectra (Fig.…”
Section: Microstructuresmentioning
confidence: 99%